Investigation of Physical and Mental Fatigue, Perceived Social Support and Quality of Life in Greek Social Workers: The Role of Demographic and Occupational Characteristics - Paraskevi Theofilou; Stavroula Malkopoulou (Journal of Public Health International, 2024)
The present study focuses on the investigation of fatigue, social support and quality of life that characterizes social workers. Furthermore, the study aims to highlight the effect of demographic and occupational characteristics on the above factors. A total of 400 social workers with an average age of 39.05 years took part in the research. Most were women, single, residents of cities of more than 100,000, and health care workers. Participants were asked to answer online questionnaires (FAS for fatigue, MSPSS for social support and GHQ-28 for quality of life). From the analysis of the data, it was found that the level of fatigue of the social workers is at low levels. At the same time, the level of occurrence of negative symptoms is also low, with physical symptoms appearing more often than the rest. Participants receive a high level of support from their environment, and more so from the
Keywords: fatigue